The Urgency of Environmental Education in Shaping Pro-Environmental Behavior Among Gen Z University Students - Arbiana Putri (EDUJAVARE: International Journal of Educational Research, 2025)
Environmental education plays a strategic role in shaping pro-environmental behavior, particularly among Generation Z university students who have grown up amidst rapid digital technological advancements and heightened awareness of sustainability issues. This study aims to describe the role of environmental education specifically within the "Environmental Education" course in fostering pro-environmental behavior among Generation Z students through the application of a project-based learning model. The findings indicate that experiential learning approaches, such as project-based learning combined with the use of digital media, make a tangible contribution to enhancing knowledge, shaping pro-environmental behavior, and promoting eco-friendly practices among Generation Z students. This learning model strengthens ecological awareness while simultaneously driving real behavioral changes within the university environment. However, the implementation of environmental education faces several challenges, including the gap between understanding and actual action (the value-action gap), limited campus support facilities, and a strong culture of consumerism that influences Generation Z students' behavior. Therefore, it is necessary to strengthen the curriculum by focusing not only on conceptual mastery but also on developing environmental action skills through behavior-based evaluations, student participation incentives, and the provision of campus policies and infrastructure that support sustainable practices. Through such a comprehensive approach, environmental education in higher education is expected to produce a young generation that possesses strong environmental literacy and acts as an agent of change, capable of initiating and disseminating sustainability practices within the wider community.